Essays on Price Discovery Measure, Exchange-Traded Funds and Liquidity - Sultan, Syed Galib (My University, 2015)
Price Discovery is the process by which new information is impounded into asset prices through trading activity. A market is considered to contribute more to price discovery if it is the first to capture new information regarding the fundamental value of an asset. Hasbrouck’s (1995) information share (IS) is the most widely used measure for price discovery contribution even though there is a well-documented concern with identification: its dependence on the ordering of the variable in the price vector and its non-uniqueness. In the first chapter, we propose a new measure, “Price Discovery Share” (PDS) that is closely related to IS and resolves the identification problems inherent in the IS method. PDS is motivated by a widely used method in risk management literature called the “risk-budgeting” or additive decomposition of portfolio volatility. Using simulated data based on different structural asset pricing models, we find that PDS measures the structural price discovery contribution more accurately than IS. In the second chapter, we apply Price Discovery Share (PDS) to investigate the “duplication of Exchange-Traded Funds (ETFs)” phenomenon, a recent institutional trend in financial markets. We show that although there are multiple ETFs tracking the S&P 500 index, one specific S&P 500 ETF (‘SPY’) always contributes more to price discovery than the rest. We also find that PDS, unlike Information Share (IS), is robust to the use of intra-day market price data sampled at different frequencies. In the third chapter, we study the effect of bond Exchange-traded funds (ETFs) and bond mutual funds on the liquidity of U.S. corporate bonds. Depending on the liquidity measure used, we find different statistically significant results. ETF ownership has a positive impact on their underlying corporate bonds liquidity when we only consider bonds that are already bought and held by ETFs. Bond mutual funds ownership is found to play a positive impact on the liquidity of high yield corporate bonds.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Bond Liquidity; Exchange-Traded Funds; Price Discovery; Economics; Finance; economics